Patient preferences and shared decision making for the traditional Chinese medicine treatment of lung cancer: A discrete choice experiment study - Yue Teng; Yan Wei; Yingyao Chen; Juntao Yan; Shimeng Liu; Fuming Li; Shiyi Bao; Yanfeng Ren; Liu Liu; Yi Yang (Integrative Medicine Research)
Background: Traditional Chinese Medicine (TCM), integrating patient preferences into decision-making process, has been widely used in the multimodality therapy of lung cancer. This study aimed to estimate patient preferences for treatment and shared decision-making (SDM) modes concerning inpatient TCM treatment of lung cancer in Shanghai in order to provide a basis for clinical decision-making process on TCM therapy for lung cancer. Methods: This study was conducted among patients (n = 347) from nine tertiary hospitals in Shanghai by discrete-choice experiment (DCE) survey and Shared Decision-Making Questionnaire-patient version (SDM-Q-9) survey. The DCE was developed with the inclusion of the most relevant attributes at appropriate levels for the TCM treatment of lung cancer. The empirical data analyses of patients were performed using mixed logit models. Additionally, subgroup analysis was conducted. Results: In total, 347 respondents completed the questionnaire. All attributes’ coefficients were statistically significant for patients’ preferences. Patients showed strong preferences for increasing disease control rate, relieving nausea and vomiting, reducing the risk of side effects, and were concerned about monthly out-of-pocket costs. Subgroup analysis indicated that patients with a lower SDM-Q-9 score and those who were satisfied with medical services emphasized more importance of higher disease control rate. Furthermore, most of the patients (90.20%) self-reported a high willingness to use SDM during the decision-making process. Conclusion: In Shanghai, patients mainly preferred SDM and considered disease control rate as the most essential attribute in the TCM treatment of lung cancer. The study findings could underscore the importance of considering patients’ preferences and promote SDM.